THE POTENTIAL DEVELOPMENT STRATEGY OF CAPTURE FISHERIES IN THE FISHERIES OFFICE OF PACITAN REGENCY - Bagoes Soenarjanto; Arif Darmawan; Achluddin Ibnu Rochim (DIA: Jurnal Administrasi Publik, 2021)
This thesis discusses the strategy of the Pacitan Regency Fisheries Service in developing the potential of capture fisheries in the spirit of regional autonomy. This research was conducted using qualitative methods through field studies and literature studies. The results of this study indicate that the Pacitan Regency Fisheries Service has several strategies that are intended to maximize the existing capture fisheries products, namely by building / rehabilitating the facilities and infrastructure for fish auction places, procuring facilities and infrastructure for empowering small-scale businesses of fishing communities, improving local facilities of landing fish, developing capture fishery facilities, optimizing capture fisheries data collection, and last is improving fishing technology. However, there are still several obstacles faced, one of which is related to insufficient budget allocation.